Changes in morning pulse, hemoglobin and BUN in female rowers during altitude training - Yan, H.; Hao, W. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. II, 2008)
The study aimed to analyze the changes in morning pulse, hemoglobin, and BUN in the female rowers during altitude training in order to find out the relationships between the indexes and sport performance.